The politics of federalism in Argentina and its implications for governance and accountability - Ardanaz, Martín (2013)
This paper contributes to an agenda that views the effects of federalism and decentralization as dependent on the incentives of national and subnational political actors. It studies the mechanisms by which subnational actors affect decisions at the central level, in the context of a highly decentralized middle-income democracy, Argentina. In this federal country, provincial actors and concerns weigh heavily on national decisions. Most Argentine provinces are dominated by entrenched elites, with limited political competition, weak division of powers, and clientelistic political linkages. Provincial dominance and national relevance reinforce each other, dragging Argentine politics toward the practices and features of its most background regions.